The Influence of Service Quality and Customer Satisfaction on Customer Loyalty at J&T Express Citeureup Branch, Cimahi, West Java - Ulfa, Nabila; Mubarok, Dadan Abdul Aziz (International Journal of Marketing & Human Resource Research, 2025)
This research was conducted to determine the effect of service quality and customer satisfaction on customer loyalty at the J&T Express branch in Citeureup Cimahi. This research uses a quantitative and verificative approach, namely, using a questionnaire instrument. The primary data used is in the form of tabulated results from questionnaire responses. The sample used by the researcher consists of customers who sent goods for 1 month at J&T Express on Jl. Kamarung No 14B, Cimahi Utara District, Cimahi City, West Java, with 96 respondents. Determination of the sample size, the researcher used the Rao Purba formula. Based on the research results that have been conducted show that service quality and customer satisfaction simultaneously have a positive and significant impact on customer loyalty at J&T Express Citeureup Branch, Cimahi, West Java. This means that the increase in service quality and customer satisfaction together can influence the level of customer loyalty at J&T Express Citeureup Branch, Cimahi, West Java